Pendampingan Perhitungan Harga Pokok Produksi Pengerajin Kecamatan Sungai Kakap Kabupaten Kubu Raya - Jaurino, Jaurino; Risal, Risal; Afif, Ali (Universitas Pahlawan Tuanku Tambusai, 2025)
Sungai Kakap District is one of nine districts in the Kubu Raya Regency Government. Sungai Kakap District has very potential natural resources. Seeing the natural potential of the Sungai Kakap District area, some of its residents develop their creativity in empowering natural resources such as Coconut Shells for crafts. Based on observations and the results of discussions with the Sub-district Head, the Calculation of Production Costs for craftsmen in Sungai Kakap District needs to be improved to be useful as a basis for determining selling prices. This Community Service activity aims to provide enlightenment and educate craftsmen in Sungai Kakap District so that they have the ability to determine the amount of production costs of their crafts. The service method is direct class. The results of this activity received a positive response and improved the craftsmen's production cost calculation skills. This activity is very important for the long-term development of craftsmen's businesses.